2022
DOI: 10.1177/08927057221147825
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a recycled nylon fiber reinforced and nano-fly ash hybridized high impact performance polypropylene composite for sustainability

Abstract: The pursuit of a renewable and recyclable material to reduce carbon footprint is the need of the hour for a safe and secure future of flora and fauna. This study explores the reinforcement potential of pre-treated recycled nylon fiber (NF) with CaCl2, NaOH and silane in a polypropylene (PP) matrix. Silane coating over the fiber surface was confirmed from FTIR and surface morphology. Interfacial interactions among NF and PP were further strengthened by adding nano-structured cetrimonium bromide (CTAB) treated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
1
6
1
Order By: Relevance
“…Moreover, if we compare the tensile strength of the other synthetic fiber reinforced polypropylene composites prepared and characterized in the past, the results reported in the current study are significantly superior. For instance, in the previous study when a similar BM was reinforced with recycled nylon fiber the highest tensile strength of 39.40 MPa was obtained 35 which is ~18% lower than the highest strength reported in the present study. In another previous study, Wang et al 40 used short glass giber (3–4.5 mm) and melt blended with polypropylene using different compatibilizer and β nucleating agent.…”
Section: Resultscontrasting
confidence: 86%
See 4 more Smart Citations
“…Moreover, if we compare the tensile strength of the other synthetic fiber reinforced polypropylene composites prepared and characterized in the past, the results reported in the current study are significantly superior. For instance, in the previous study when a similar BM was reinforced with recycled nylon fiber the highest tensile strength of 39.40 MPa was obtained 35 which is ~18% lower than the highest strength reported in the present study. In another previous study, Wang et al 40 used short glass giber (3–4.5 mm) and melt blended with polypropylene using different compatibilizer and β nucleating agent.…”
Section: Resultscontrasting
confidence: 86%
“…Comparatively, in the past Khan et al, 42 used 50 wt% E‐glass fiber mat to reinforce the PP matrix and demonstrated a flexural strength of 85 MPa only. Likewise, recycled nylon fiber reinforced BM has been reported earlier to possess a flexural strength of 53.60 MPa 35 . This demonstrates the superior reinforcing efficiency of BF and submicron particles of FA for the PP matrix.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations